2003
DOI: 10.1145/949952.940105
|View full text |Cite
|
Sign up to set email alerts
|

Towards scalable compositional analysis by refactoring design models

Abstract: Automated finite-state verification techniques have matured considerably in the past several years, but state-space explosion remains an obstacle to their use. Theoretical lower bounds on complexity imply that all of the techniques that have been developed to avoid or mitigate state-space explosion depend on models that are "well-formed" in some way, and will usually fail for other models. This further implies that, when analysis is applied to models derived from designs or implementations of actual software s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…7(b) that the action stop is, in fact, unreachable. 5 There is no way to efficiently enumerate all execution paths because the enumeration problem is exponential in complexity. In the proposed technique, we only aim at a balance between practicality and completeness.…”
Section: Limitation Analysismentioning
confidence: 99%
“…7(b) that the action stop is, in fact, unreachable. 5 There is no way to efficiently enumerate all execution paths because the enumeration problem is exponential in complexity. In the proposed technique, we only aim at a balance between practicality and completeness.…”
Section: Limitation Analysismentioning
confidence: 99%
“…That is, no feasible subsystems and composing hierarchies exist in this structure, particularly when client number is large. In [4,5], we proposed an approach called model refactoring to enable compositional analysis for systems which are originally prohibited by their as-built architecture. The refactoring consists a set of transformations.…”
Section: Model Refactoringmentioning
confidence: 99%
“…In [5], we described the basic tool support 3 for refactoring and showed that a refactored elevator system can be analyzed up to hundreds of elevators but global analysis and compositional analysis (without refactoring) can only analyze up to 4 elevators.…”
Section: Model Refactoringmentioning
confidence: 99%
See 1 more Smart Citation